FES avid pulmonary adenocarcinoma and confounding ER+ breast carcinoma - Yousif M. Abdelmoneim, MD; Yanyan Lou, MD PhD; Pooja Advani, MD; Andras Khoor, MD PhD; Akash Sharma, MD; Ephraim E. Parent, MD PhD (Radiology Case Reports)
Breast carcinomas are well known for expression of estrogen receptor (ER) however there are other malignancies that are also express ER, possibly confounding the diagnostic interpretation of 16α-[18F]fluoro-17β-estradiol (FES; Cerianna GE HealthCare) in patients with both ER+ breast carcinomas and other malignancies. We present a case of a woman with prior history of both ER+ breast carcinoma and pulmonary adenocarcinoma with subsequent identification of an FES pulmonary nodule that was proven on histopathology to be consistent with an ER expressing pulmonary adenocarcinoma metastasis